DIFFERENCES IN BODY COMPOSITION AND HANDGRIP STRENGTH AMONG 12–15-YEAR-OLD FOOTBALL PLAYERS FROM NORTHEASTERN ROMANIA - TROFIN, Florin-Petruț; HONCERIU, Cezar (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: Early adolescence is marked by a series of anatomical and functional changes. Understanding these functional adaptations is particularly relevant for football coaches, as they influence training strategies and performance development. Objective: This study aimed to examine age-related differences in body composition parameters and handgrip strength among junior football players. Materials and Methods: Between September 2024 and August 2025, 151 male football players aged 12 (n=18), 13 (n=35), 14 (n=45), and 15 years (n=53) were assessed. Handgrip dynamometry is widely recognized in literature as a reliable measure of overall muscular strength in athletes. Two Constant hand dynamometers (model 14192-760E) were used, with participants performing maximal voluntary contractions while standing, arms fully extended and held obliquely laterally. Results: Significant anthropometric increases were observed between ages 13 and 14, whereas BMI remained consistent across age groups. Muscle mass increased from 39.06 ± 2.21% at age 13 to 41.09 ± 1.37% at age 14, while body fat percentage did not change significantly. No significant differences were observed in handgrip strength, despite notable changes in body composition. Conclusions: Handgrip strength assessment represents a practical tool for monitoring and evaluating muscular strength in adolescent athletes. The data provided by this study may serve as reference values for coaches in the region. In this cohort, early adolescence was associated with nonsignificant changes in handgrip strength, despite measurable alterations in body composition.